ANTIQUE-ART APPRAISAL MODEL STANDARD INDONESIAN MUSEUM - Timbul Raharjo, Mikke Susanto, Moh. Rusnoto Susanto, Syed Muhd Hafiz, Mita Purbasari Wahidiyat, Kukuh Pamuji, Rio Septian (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This appraisal model study is called MABAS, which aims to make decisions on calculating anti-art objects in museum or gallery collections with an estimated value of fair prices. In Indonesia, there is no standard appraisal method to determine the economic value of anti-art objects. It is predicted that there will be thousands of collections of anti-art objects in museums throughout Indonesia and their economic value is unknown. This calculation model uses an approach to material costs and labor (production) costs. The MABAS appraisal method specifically adds calculation value to the main factor, namely intangible explanatory variables, including cultural heritage, history, beauty, originality, rarity, function, acquisition, media publication, depreciation, and coefficient. In the initial research, this model was tested on objects in the collection of the Indonesian presidential palace. Then in this further research, a sampling test was carried out on the collection of the National Museum of the Republic of Indonesia.